Computer Aided Development of Nucleic Acid Applications in Nanotechnologies - Paloncýová, Markéta; Pykal, Martin; Kührová, Petra; Banáš, Pavel; Šponer, Jiří; Otyepka, Michal (Small (Weinheim an der Bergstrasse, Germany), 2022)
Utilization of nucleic acids (NAs) in nanotechnologies and nanotechnology-related applications is a growing field with broad application potential, ranging from biosensing up to targeted cell delivery. Computer simulations are useful techniques that can aid design and speed up development in this field. This review focuses on computer simulations of hybrid nanomaterials composed of NAs and other components. Current state-of-the-art molecular dynamics simulations, empirical force fields (FFs), and coarse-grained approaches for the description of deoxyribonucleic acid and ribonucleic acid are critically discussed. Challenges in combining biomacromolecular and nanomaterial FFs are emphasized. Recent applications of simulations for modeling NAs and their interactions with nano- and biomaterials are overviewed in the fields of sensing applications, targeted delivery, and NA templated materials. Future perspectives of development are also highlighted.
Keywords: Computers; nukleové kyseliny; lipid nanoparticles; nucleic acid templated assemblies; Nucleic Acids; nucleic acids; nanotechnologie; Nanotechnology; MD simulations; force fields; počítače; biosensors